Contemporary Tools for Regulating Gene Expression in Bacteria. Issue 3 (March 2020) - Kent, Ross; Dixon, Neil
Abstract : Insights from novel mechanistic paradigms in gene expression control have led to the development of new gene expression systems for bioproduction, control, and sensing applications. Coupled with a greater understanding of synthetic burden and modern creative biodesign approaches, contemporary bacterial gene expression tools and systems are emerging that permit fine-tuning of expression, enabling greater predictability and maximisation of specific productivity, while minimising deleterious effects upon cell viability. These advances have been achieved by using a plethora of regulatory tools, operating at all levels of the so-called 'central dogma' of molecular biology. In this review, we discuss these gene regulation tools in the context of their design, prototyping, integration into expression systems, and biotechnological application. Highlights: A huge array of genetic regulatory tools are now available that permit gene expression control at all layers of the central dogma. Matching production demand with cellular capacity can reduce burden and allow stable production over longer timescales. Modern in silico design tools allow rapid design and optimisation of complex genetic circuitry. Cell-free prototyping of genetic parts and devices is an emerging, yet powerful tool to improve the design–build–test–learn cycle. The use of feedback loops to facilitate dynamic regulation of gene expression allows researchers to construct responsive pathways to minimise cellular metabolic burden. Stress-linked expression regulation enables coupling of heterologous production with endogenous stress response pathways.